Job satisfaction and associated factors in Greek public hospitals - Karaferis, Dimitris; Aletras, Vassilis; Niakas, Dimitris (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: To investigate the level of job satisfaction of health care professionals in the public hospitals of the 1st Regional Health Authority of Attica and further to assess its determining factors. Methods: The Job Satisfaction Survey questionnaire was administered to health professionals in thirteen hospitals. The 36 items of the questionnaire are expressed on a Likert scale and are divided into nine dimensions. Additional questions were added covering the demographic and socio-economic characteristics. Results: The reliability of the tool was: α Cronbach = 0.89. The response rate was 81.95%, 3,278 questionnaires were collected overall, of which 52,96% (n=1,736) originated from the nursing staff, 24.50% (n=803) from the medical staff and 22.54% (n=739) from other health employees. The average overall job satisfaction is moderate (3.33 out of 6). The category with the lowest score in job satisfaction was that concerning salaries (2.12). Questions related to promotion (2.45), additional benefits (2.67), operating procedures (2.82) received low job satisfaction rates. Instead, the categories that garnered positive job satisfaction concerned questions related to the supervision (4.66), the nature of work (4.34), and co-workers (4.25). Questions related to communication received 3.79. Conclusions: The findings showed lowest satisfaction levels in pay, fringe benefits, contingent rewards, promotion and operating procedures dimensions of job satisfaction. Participants were more satisfied with the nature of work, supervision and co-workers. The findings can be used as a set of reference levels and indicators for the human resources development component of the quality management system in the public hospitals.